Characteristics of falls occurring during rehabilitation in an acute care hospital in older and non-older patients: A retrospective cohort study - Kinoshita, Tokio; Nishimura, Yukihide; Umemoto, Yasunori; Kawasaki, Shinji; Yasuoka, Yoshinori; Minami, Kohei; Koike, Yumi; Tajima, Fumihiro (Frontiers in Medicine, 2022)
Introduction: Although falls are often reported in hospitals and are common in older individuals, no reports on falls during rehabilitation exist. This study evaluated patients with falls occurring during rehabilitation and identified the characteristics of older and non-older patients. Methods: Our study retrospectively analyzed reports of falls occurring during rehabilitation at a university hospital from April 1, 2020 to March 31, 2022. The survey items included the number of falls in the hospital as a whole and during rehabilitation, age, gender, modified Rankin Scale (mRS) before admission and at the time of fall, functional independence measure (FIM) at admission, patient communication status at the time of fall, and whether a therapist was near the patient. Patients aged ≥65 were considered older; aged ≤64, non-older; and those with the same age, gender, and clinical department, randomly selected as non-falling patients. Results: Thirty-five falls occurred during rehabilitation (14 in the non-older and 21 in the older patients), significantly lower than the 945 for the hospital as a whole, without any significant difference between non-older and older patients. No significant differences in mRS before admission and FIM at admission were noted for both groups in comparison with the non-falling patient group. Furthermore, gender, mRS, FIM, good communication status, or presence of therapist being near the patient did not differ when comparing non-older and older patients (non-older 71.4%, older 52.4%). Most falls were minor adverse events that did not require additional treatment. Conclusion: The rate of falls during rehabilitation was much lower than that during hospitalization, and many falls had minimal impact on the patient. It was also difficult to predict falls in daily life and communication situations, and there was no difference in characteristics between the older and non-older groups. Since more than half of the falls occurred during training with the therapist, it is necessary to reconsider the training content.